Stakeholders engagement in emergency response of flood disasters management in District Ijen, Bondowoso Regency, Indonesia - Rustinsyah, Rustinsyah; Prasetya, Djoko Adi (Jurnal Sosiologi Dialektika, 2023)
The recurring flash floods in Ijen District, Bondowoso, has caused damage to houses and villages infrastructures. Flood handling requires coordination from multiple stakeholders, social enterprises and Non-Governmental Organizations. This study explores the stakeholders' involvement in the emergency response of flash flood disaster handling in the Ijen District. This study used qualitative and quantitative approaches. The study found that these stakeholders have their own aims and interests. The analysts predict that the power index value is 0.74, while the interest index value is 0.94. These two figures show that both the power and the interests of the stakeholders are very high in dealing with flash flood disasters. Despite the high values, until August 2020, the recovery process had not been completed yet. These findings are important as an evaluation of the emergency response in disaster handling and a warning that it is important to sustain the environmental condition of mountain slopes